CELSR2, encoding a planar cell polarity protein, is a putative gene in Joubert syndrome with cortical heterotopia, microophthalmia, and growth hormone deficiency. Issue 3 (4th January 2017) - Vilboux, Thierry; Malicdan, May Christine V.; Roney, Joseph C.; Cullinane, Andrew R.; Stephen, Joshi; Yildirimli, Deniz; Bryant, Joy; Fischer, Roxanne; Vemulapalli, Meghana; Mullikin, James C.; ,; Steinbach, Peter J.; et al.
Abstract : Joubert syndrome is a ciliopathy characterized by a specific constellation of central nervous system malformations that result in the pathognomonic "molar tooth sign" on imaging. More than 27 genes are associated with Joubert syndrome, but some patients do not have mutations in any of these genes. Celsr1, Celsr2, and Celsr3 are the mammalian orthologues of the drosophila planar cell polarity protein, flamingo; they play important roles in neural development, including axon guidance, neuronal migration, and cilium polarity. Here, we report bi‐allelic mutations in CELSR2 in a Joubert patient with cortical heterotopia, microophthalmia, and growth hormone deficiency. © 2017 Wiley Periodicals, Inc.